Readiness to Successful Hybrid Learning as Part of Competitive Advantages through Students’ Experiences in New Normal - Shiyrah Theosebes Sela; Dudi Permana (International Humanities and Applied Science Journal, 2022)
This paper examines the readiness of a technology-based non-state university in Jakarta, Indonesia in conducting hybrid learning as part of competitive advantages based on the students’ experiences. The discussion only focuses on the hybrid learning implementation in new normal to identify the readiness of the university in conducting it and to claim it as one of the competitive advantages. In order to support the claim, questionnaire has been spread to collect data from students who experience the hybrid learning implementation directly. Online questionnaire on Microsoft Forms sent to students through social media network. This is the green method to save resources in collecting data. The collected data shows how the hybrid learning implemented in learning process of each student as respondent of this research. The result will confirm the hybrid learning implementation in this university can be claimed as the competitive advantage and enrich the researches related to competitive advantages in education fields.